2016
DOI: 10.1111/rode.12230
|View full text |Cite
|
Sign up to set email alerts
|

Do Employers' Responses to Crises Impact Men and Women Differently? Firm‐level Evidence from Indonesia

Abstract: Do employers' responses to crises impact men and women differently? Using manufacturing census data from Indonesia this paper assesses gender differences in the impact of the East Asian crisis and to what extent these were due to differential treatment of men and women within firms and gender sorting across firms that varied in their exposure to the crisis. On average, women experienced higher job losses than their male colleagues within the same firm. However, the aggregate adverse effect of such differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(49 reference statements)
1
0
0
Order By: Relevance
“…Lim (2000) looked at the e ects of the East Asian crisis in the Philippines and found that while women were displaced more in the manufacturing sector, they overall su ered less from the crisis as sectors with high female employment such as social and personal services, trade, and wholesale were hit less hard. Similar results are found by Hallward-Driemeier et al (2017) that examined how variations in rms' responses during the East Asian crisis in Indonesia a ected men's and women's relative employment vulnerability. ey found that women experienced higher job losses than their male colleagues within the same rm.…”
Section: Introductionsupporting
confidence: 75%
“…Lim (2000) looked at the e ects of the East Asian crisis in the Philippines and found that while women were displaced more in the manufacturing sector, they overall su ered less from the crisis as sectors with high female employment such as social and personal services, trade, and wholesale were hit less hard. Similar results are found by Hallward-Driemeier et al (2017) that examined how variations in rms' responses during the East Asian crisis in Indonesia a ected men's and women's relative employment vulnerability. ey found that women experienced higher job losses than their male colleagues within the same rm.…”
Section: Introductionsupporting
confidence: 75%